2017
DOI: 10.18203/2349-2902.isj20171618
|View full text |Cite
|
Sign up to set email alerts
|

Modified Graham’s repair for peptic ulcer perforation: reassessment study

Abstract: Background: Peptic perforation is an emergency and requires urgent surgical treatment. Many modalities of treatment are available ranging from conservative treatment to laparoscopic repair. There is no consensus on treatment of perforated pylorodudenal ulcer which can be treated with conservative treatment, simple closure of ulcer, closure of ulcer with free omentum, closure of perforation with use of pedicled omentum, definitive treatment with truncal vagotomy and drainage procedures or parietal cell vagotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…Higher frequency in males was also observed in similar studies done on perforation peritonitis. 6,7,8 The common encountered age group between 41-50 years in some studies, is also observed in case of females in the present study. 9,10 Perforation was found to be common in males between 35-45 yrs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Higher frequency in males was also observed in similar studies done on perforation peritonitis. 6,7,8 The common encountered age group between 41-50 years in some studies, is also observed in case of females in the present study. 9,10 Perforation was found to be common in males between 35-45 yrs.…”
Section: Discussionsupporting
confidence: 82%
“…of age group and in case of females older age group between 40 to 65 years is observed in a study which is quite similar to the present study. 6 In our study majority cases were associated with positive history of acid peptic disease 69.4%, other risk factors included were tobacco chewing & smoking in 37%, alcohol in 25%, drug abuse in 18.5% cases (Table-2). 60 cases of perforation peritonitis reported in a study show positive history of smoking and alcoholics with occasional use of NSAIDs in 43 males while 8 female were associated with using only NSAIDs and 9 cases were not found to be associated with risk factors 6 .…”
Section: Discussionmentioning
confidence: 48%
“…[6][7][8] Surgical management remains the corner stone in perforated ulcers. [9][10][11] Traditional open surgical method is usually undertaken. Simple closure with or without Omentum is one of the most commonly used technique.…”
Section: Discussionmentioning
confidence: 99%
“…Simple closure with or without Omentum is one of the most commonly used technique. 10 Time should not be wasted after clinical diagnosis for surgery as it can lead to adverse results. In children partial gastrectomy is seldom advised even though in adults for large perforations it is being carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation